Influence of Feed Satisfaction Interval on Survival and Growth of Patin (Pangasius hypopthalmus) - Meika Puspita Sari; Helmizuryani helmizuryani; Sukma Adjie; Khusnul Khotimah (Journal of Global Sustainable Agriculture, 2022)
This study aims to determine the effect of the fasting interval on the growth of length and weight during maintenance in Pangasius hypophthalmus-fed pellets. The study was conducted in the hatchery laboratory of the Aquaculture Study Program, Faculty of Agriculture, University of Muhammadiyah Palembang, utilizing the completely random Desain (RAL) method with five treatments and three repetitions. P1 was fed daily (control), P2 was fasted for one day and fed for one, P3 was fasted for one day and fed for two, P4 was fasted for one day and fed for three, and P5 was fasted for one day and fed for four.P1 was fed daily (control), P2 was fasted for one day and fed for one, P3 was fasted for one day and fed for two, P4 was fasted for one day and fed for three, and P5 was fasted for one day and fed for four.The data were then analyzed using an ANOVA test to determine the effect of each treatment.The data were then analyzed using an ANOVA test to determine the effect of each treatment. The best results for long growth were obtained from the P2 treatment, and the best results for weight growth were obtained from the P2 treatment. During the observations, P2 demonstrated the highest survival rate. The P5 treatment indicates the highest feed utilization efficiency and feed conversion ratio with values of 69 percent and 1.67 percent, respectively. The feeding intervals with fasting treatment produced the best results in terms of growth, fed efficiency, and feed conservation; however, there was no significant difference in the observation factor.